Genomics-based diagnostic marker development for Xanthomonas oryzae pv. oryzae and X. oryzae pv. oryzicola. - Lang, Jillian M.; Hamilton, John P.; Diaz, Maria Genaleen Q.; Van Sluys, Marie Anne; Burgos, Ma. Ruby G.; Vera Cruz, Casiana M.; Buell, C. Robin; Tisserat, Ned A.; Leach, Jan E. (Scientific Societies, 2010)
A computational genomics pipeline was used to compare sequenced genomes of Xanthomonas spp. and to rapidly identify unique regions for development of highly specific diagnostic markers. A suite of diagnostic primers was selected to monitor diverse loci and to distinguish the rice bacterial blight and bacterial leaf streak pathogens, Xanthomonas oryzae pv. oryzae and X. oryzae pv. oryzicola, respectively. A subset of these primers was combined into a multiplex polymerase chain reaction set that accurately distinguished the two rice pathogens in a survey of a geographically diverse collection of X. oryzae pv. oryzae, X. oryzae pv. oryzicola, other xanthomonads, and several genera of plant-pathogenic and plant- or seed-associated bacteria. This computational approach for identification of unique loci through whole-genome comparisons is a powerful tool that can be applied to other plant pathogens to expedite development of diagnostic primers.